2012
DOI: 10.1007/s13193-012-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

Is the 1-cm Rule of Distal Bowel Resection Margin in Rectal Cancer Based on Clinical Evidence? A Systematic Review

Abstract: Background. Distal intramural spread is present within 1 cm from visible tumor in a substantial proportion of patients. Therefore, C1 cm of distal bowel clearance is recommended as minimally acceptable. However, clinical results are contradictory in answering the question of whether this rule is valid. The aim of this review was to evaluate whether in patients undergoing anterior resection, a distal bowel gross margin of \1 cm jeopardizes oncologic safety. Methods. A systematic review of the literature identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 31 publications
(97 reference statements)
3
57
2
Order By: Relevance
“…The results of our review of low-lying tumours in irradiated patients are in line with the results of two recent systematic reviews that included all patients regardless of tumour location within the rectum [4,5]. One of these reviews, reported by our group, identified 17 studies including 5903 patients [4]. Regardless of cutoff point (1 cm, 5 mm or 2 mm) or whether radiotherapy was delivered or not the meta-analysis showed that the differences in the local recurrence rate between the small margin groups and the large margin groups was not statistically significant.…”
Section: Evidence From Publications That Included All Patients Regardsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of our review of low-lying tumours in irradiated patients are in line with the results of two recent systematic reviews that included all patients regardless of tumour location within the rectum [4,5]. One of these reviews, reported by our group, identified 17 studies including 5903 patients [4]. Regardless of cutoff point (1 cm, 5 mm or 2 mm) or whether radiotherapy was delivered or not the meta-analysis showed that the differences in the local recurrence rate between the small margin groups and the large margin groups was not statistically significant.…”
Section: Evidence From Publications That Included All Patients Regardsupporting
confidence: 84%
“…The results of our review of low-lying tumours in irradiated patients are in line with the results of two recent systematic reviews that included all patients regardless of tumour location within the rectum [4,5]. One of these reviews, reported by our group, identified 17 studies including 5903 patients [4].…”
Section: Evidence From Publications That Included All Patients Regardsupporting
confidence: 83%
“…The cut of values for the subgroups were set theoretically, based on previously published reports 23 - 28 . We observed 4 (14.8%) deaths due to rectal cancer in Group I, 6 (19.4%) in Group II and 12 (23.5%) in Group III.…”
Section: Discussionmentioning
confidence: 92%
“…All the specimens were histopathologically tested for all the resection margins, including the circumferential resection margin; if any of the margins were positive, patients were excluded from the study (R1 resection). One of the most comprehensive systematic reviews of the literature was published by Bujko et al 23 . In this review authors identified 17 studies showing results in relation to margins < 1 cm versus > 1 cm, five studies in relation to a margin ≤ 5 mm versus ≥ 5 mm and five studies showing results in a margin of ≤ 2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In another retrospective study of 218 rectal cancer patients, Hong et al [25] compared groups of patients with DRM length of >2 cm, 1-2 cm, and <1 cm and did not find any statistically significant difference in overall survival or local recurrence rates. Bujko et al [26] performed a systematic review of literature and a pooled analysis of studies comparing recurrence rates for DRMs of 10, 5, and 2 mm and demonstrated that the local recurrence rates were 1% more with margin of <1 cm, 1.7% more with margin of 5 mm, and 2.7% with margin of 2 mm, and concluded that a DRM of <1 cm did not compromise oncologic safety. Although interpreting the above data, one should keep in mind that most studies measuring DRM length use a variety of specimen processing techniques including fixed [13,20,21] versus unfixed [4,8] and pinned [13] versus unpinned [4,8,21] specimens.…”
Section: Drm and Oncologic Outcomesmentioning
confidence: 99%